Evaluation of platelet function in essential thrombocythemia under different analytical conditions. (17th February 2020) - Lussana, Federico; Femia, Eti Alessandra; Pugliano, Mariateresa; Podda, Gianmarco; Razzari, Cristina; Maugeri, Norma; Lecchi, Anna; Caberlon, Sabrina; Gerli, Giancarla; Cattaneo, Marco
Abstract: Background . Studies of platelet aggregation (PA) in essential thrombocythemia (ET) reported contrasting results, likely due to differences in analytical conditions. Objective . We investigated platelet aggregation using different techniques and analytical conditions. Patients and Methods . PA was studied by light-transmission aggregometry (LTA) in platelet-rich plasma (PRP) and impedance aggregometry in PRP and whole blood (WB). ADP, collagen, thrombin receptor activating peptide (TRAP-14) and adrenaline were used as agonists. Since ET patients (n = 41) were on treatment with aspirin (100 mg/d), healthy controls (n = 29) were given aspirin (100 mg/d) for 5 days before testing: therefore, thromboxane A2 -independent PA was tested in all subjects. Blood samples were collected in citrate (C) [low Ca 2+ ] or lepirudin (L) [physiological Ca 2+ ]; platelet count was adjusted to 250 x 10 9 /L in a set of C-PRP (adjusted C-PRP) and left unmodified in the other samples. Results . Results of PA in 17 ET patients who were poor responders to aspirin (high serum thromboxane B2 levels) were not included in the analysis. With LTA, PA in ET was lower than in controls in adjusted C-PRP and normal in native C-PRP and L-PRP. With impedance aggregometry, PA in L-PRP and L-WB tended to be higher in ET than in controls. Platelet serotonin and ADP contents were reduced in ET. The percentages of circulating platelets expressing P-selectin and platelet-leukocyte hetero-aggregates were higher in ET. Conclusions . Analytical conditions dramatically affect in vitro PA of ET patients, which appears defective under the least physiological conditions and normal/supranormal under conditions that are closer to the physiological.